Resveratrol Ameliorates the Anxiety- and Depression-Like Behavior of Subclinical Hypothyroidism Rat: Possible Involvement of the HPT Axis, HPA Axis, and Wnt/β-Catenin Pathway - Ge, Jin-Fang; Xu, Ya-Yun; Qin, Gan; Cheng, Jiang-Qun; Chen, Fei-Hu (Frontiers in Endocrinology, 2016)
Metabolic disease subclinical hypothyroidism (SCH) is closely associated with depression-like behavior both in human and animal studies, and our previous studies have identified the antidepressant effect of resveratrol (RES) in stressed rat model. The aim of this study was to investigate whether RES would manifest an antidepressant effect in SCH rat model and explore the possible mechanism. A SCH rat model was induced by hemi-thyroid electrocauterization, after which the model rats in the RES and LT4 groups received a daily intragastric injection of RES at the dose of 15 mg/kg or LT4 at the dose of 60 μg/kg for 16 days, respectively. The rats’ plasma concentrations of thyroid hormones were measured. Behavioral performance and hypothalamic-pituitary-adrenal (HPA) activity were evaluated. The protein expression levels of the Wnt/β-catenin in the hippocampus were detected by western blot. The results showed that RES treatment down-regulated the elevated plasma thyroid stimulating hormone (TSH) concentration and the hypothalamic mRNA expression of thyrotropin releasing hormone (TRH) in the SCH rats. RES-treated rats showed increased rearing frequency and distance in the OFT, increased sucrose preference in the SPT, and decreased immobility in the FST compared with SCH rats. The ratio of the adrenal gland weight to body weight, the plasma corticosterone levels and the hypothalamic CRH mRNA expression were reduced in the RES-treated rats. Moreover, RES treatment up-regulated the relative ratio of phosphorylated-GSK3β (p-GSK3β)/GSK3β and protein levels of p-GSK3β, cyclinD1 and c-myc, while down-regulating the relative ratio of phosphorylated-β-catenin (p-β-catenin)/β-catenin and expression of GSK3β in the hippocampus. These findings suggest that RES exerts anxiolytic- and antidepressant-like effect in SCH rats by down-regulating hyperactivity of the HPA axis and regulating both the HPT axis and the Wnt/β-catenin pathway.